Implementation of the Village Youth Youth Organization Program in an Effort to Increase Awareness in Development in Timbang Deli Village, Galang District, Deli Serdang Regency - Cindy Yulvika (International Journal of Cultural and Social Science, 2020)
This research was based on the activities of youth groups in thevillage of Timbang Deli who have the potential to contribute to thecommunity and are seen maximally in carrying out an activity inthe village. The research method used is descriptive qualitative withdata sources taken are primary data, primary data is interviews, andthe second data is secondary data in the form of documentcollection. The purpose of this research is to show that young peoplecan also participate in developing the village with every potentialthey have. The result of this research is that good developmentcommunication can help the form of Karangtaruna empowerment inthe development of a serial village in the village of Timbang Deli,implemented by optimizing the role of youth through villageactivities ranging from small positive activities such as mutualcooperation and other social activities.